Efectos secundarios del implante subdérmico - Boyso Avalos, Ma. Del Rosario (Universidad Michoacana de San Nicolás de Hidalgo, 2012)
The contraceptive methods depending on the possibility of recovering the fertility are classified in permanent weathers and. The long play one includes to implants subdermal. Single-rod subdermal Implant is a new contraceptive method that releases etonogestrel that it provides contraceptive protection by three years. The contraceptives with single progestina, it is associated with a great variety of adverse effect, the alteration in the patterns of bleed vaginal is but the common one and is the main cause by which the women discontinued use the method, in addition to migraine, mastalgia, feels nauseous and vertigo those who follow in prevalence. Objectives. To know as they are the adverse effects more frequent than it produces implants subskin in women of the UMF Nº 80. Material and methods. Retrospective, observational, cross-sectional study. 88 patients studied, I am made a questionnaire to them with identification card, adverse effect, satisfaction, application and retirement date of implant subdermal. Statistical analysis. The results appeared in total numbers, percentage and measures of central tendency like the average. Results La average age of our study was of 26 years, 50% with a son, 89, 7% with a sexual pair, with respect to the adverse effects were 65% not related to the menstruation, the changes in the menstrual pattern that less were tolerated was the prolonged bleed one, were 17 discontinued and the most frequent cause of the prolonged bleeding episodes one, 3 pregnancies appeared. Conclusions. The adverse effects related to the most frequent menstruation were not the increase of weight, whereas the menstrual changes that worried more to the patients were the prolonged bleed amenorrhea and, the continuity was of 80.6%.

Los métodos anticonceptivos dependiendo de la posibilidad de restaurar la fertilidad se clasifican en temporales y permanentes. Los de larga duración incluyen al implante subdérmico. El Implante subdérmico único es un nuevo método anticonceptivo que libera etonogestrel, que proporciona protección anticonceptiva por tres años. Los anticonceptivos con progestina sola, se asocia con una gran variedad de efectos secundarios, la alteración en los patrones de sangrado vaginal es el mas común y es la causa principal por la que las mujeres dejan de utilizar el método, además de cefalea, mastalgia, nausea y vértigo los que siguen en prevalencia. Objetivos. Conocer cuales son los efectos adversos más frecuentes que produce el implante subdérmico en mujeres de la UMF Nº 80. Material y métodos. Estudio retrospectivo, observacional, transversal. Se estudiaron 88 pacientes, se les realizo un cuestionario con ficha de identificación, efectos secundarios, satisfacción, fecha de aplicación y retiro del implante subdérmico. Análisis estadístico. Los resultados se presentaron en números totales, porcentajes y medidas de tendencia central como la media. Resultados. La edad media de nuestro estudio fue de 26 años, el 50% con un hijo, 89.7% con una pareja sexual, respecto a los efectos adversos se encontraron 65% no relacionados con la menstruación, los cambios en el patrón menstrual que menos se toleraron fue el sangrado prolongado, hubo 17 abandonos y la causa más frecuente fue sangrado prolongado, se presentaron 3 embarazos. Conclusiones. Los efectos adversos no relacionados con la menstruación más frecuente fue el incremento de peso, mientras que los cambios menstruales que más preocuparon a las pacientes fueron la amenorrea y sangrado prolongado, la continuidad fue de 80.6%.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4186; info:eu-repo/classification/cti/3; FCMB-E-2012-0086; Secundarios; Implante; Subdérmico